Innovation and competitiveness: micro and small enterprises of agroindustrial sector in Cúcuta - Hernández-Fuentes, Sharyn Nataly; Sánchez-Mojica, Karla Yohana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Globalization is an important factor in the decision-making of countries and companies to enter the reality where innovation is the main component to boost competitiveness. The objective of the research is to analyze business innovation as the axis of competitiveness for micro-enterprises and small agro-industrial companies in Cúcuta. A discrete choice model for a sample of companies in the agro-industrial sector is used for methodological purposes. This research has a mixed approach: descriptive - explanatory scope, creating the need to study the generation of business innovation. The results show that micro-enterprises and small companies in the agro-industrial sector of Cúcuta should improve their capacity to innovate in process, product and organization to be more competitive. Cúcuta, the frontier and second most unemployed city in Colombia, needs business innovation to achieve competitiveness and improve its social conditions from the business point of view.